Grain‐scale dependency of metamorphic reaction on crystal plastic strain. (19th March 2019) - Chapman, Timothy; Clarke, Geoffrey L.; Piazolo, Sandra; Robbins, Victoria A.; Trimby, Patrick W.
Abstract: The Breaksea Orthogneiss in Fiordland, New Zealand preserves water‐poor intermediate and mafic igneous rocks that were partially recrystallized to omphacite granulite and eclogite, respectively, at P  ≈ 1.8 GPa and T  ≈ 850°C. Metamorphic reaction consumed plagioclase and produced grossular‐rich garnet, jadeite‐rich omphacite, clinozoisite and kyanite. The extent of metamorphic reaction, identified by major and trace element composition and microstructural features, is patchy on the grain and outcrop scale. Domains of re‐equilibration coincide with areas that exhibit higher strain suggesting a causal link between crystal plastic strain and metamorphic reaction. Quantitative orientation analysis (EBSD) identifies gradual and stepped changes in crystal lattice orientations of igneous phenocrysts that are surrounded by homophase areas of neoblasts, characterized by high grain boundary to volume ratios and little to no internal lattice distortion. The narrow, peripheral compositional modification of less deformed garnet and omphacite phenocrysts reflects limited lattice diffusion in areas that lacked three‐dimensional networks of interconnected low‐angle boundaries. Low‐angle boundaries acted as elemental pathways (pipe diffusion) that enhanced in‐grain element diffusion. The scale of pipe diffusion is pronounced in garnet relatively to clinopyroxene. Strain‐induced mineral transformation largely controlled the extent of high‐ T metamorphic reaction under relatively fluid‐poor conditions.